1998
DOI: 10.1089/thy.1998.8.353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroid Hormone on Catecholamine and its Metabolite Concentrations in Rat Cardiac Muscle and Cerebral Cortex

Abstract: Clinical and experimental data suggest that thyroid hormone affects the actions of catecholamine (CA). However, the serum or tissue levels of CA during thyroid disorders have not been well defined. Accordingly, we investigated the levels of CA and their metabolites in the cardiac muscle, the cerebral cortex, and the plasma of rats with hyperthyroidism and hypothyroidism versus euthyroid animals. The Neurochem analyzer system (ESA, Inc., Bedford, MA) was used in such determinations. The cardiac muscles of hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…This effect is mediated by promoting BNP gene transcription (22) or by regulating the rate of transcription of the ␤-1-adrenergic receptor gene (23). Accordingly, increased and decreased NT-proBNP levels have been observed in patients with hyperthyroidism or hypothyroidism, respectively (24), and parallel changes in the levels of catecholamine and catecholamine metabolites have been shown in cardiac muscle of rats with thyroid disorders (25). Similarly, decreased aldosterone circulating levels have been observed in hypothyroid patients treated with synthetic thyroid hormones (26).…”
Section: Discussionmentioning
confidence: 96%
“…This effect is mediated by promoting BNP gene transcription (22) or by regulating the rate of transcription of the ␤-1-adrenergic receptor gene (23). Accordingly, increased and decreased NT-proBNP levels have been observed in patients with hyperthyroidism or hypothyroidism, respectively (24), and parallel changes in the levels of catecholamine and catecholamine metabolites have been shown in cardiac muscle of rats with thyroid disorders (25). Similarly, decreased aldosterone circulating levels have been observed in hypothyroid patients treated with synthetic thyroid hormones (26).…”
Section: Discussionmentioning
confidence: 96%
“…20 The hypothyroid state has been associated with dopaminergic dysfunction in animal models 21 and abnormalities in catecholamine levels, 22 and patients with RLS are believed to have an impairment of the dopaminergic pathway. 4 In our study on lung transplant recipients, all 4 patients with hypothyroidism had RLS, 5 despite normal thyroid function tests.…”
Section: Discussionmentioning
confidence: 99%
“…However, Mano et al (1998) reported that there was no difference in body weight between hypothyroid and control rats. Changes in body mass of animals with thyroid dysfunction are probably associated with a longer period of disease occurrence and the induction period has not allowed the observation of such occurrence in Mano et al (1998) study.…”
Section: Discussionmentioning
confidence: 98%
“…Changes in body mass of animals with thyroid dysfunction are probably associated with a longer period of disease occurrence and the induction period has not allowed the observation of such occurrence in Mano et al (1998) study. As regards the W.P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation